The temporal trend of women’s cancer in Changle, China and a migrant epidemiological study - Chen, Yu; Song, Mengjie; Zhang, Yanyu; Yu, Xingxing; Zou, Shuqing; Zhu, Pingxiu; Zhou, Yulin; Yang, Haomin (Frontiers in Oncology, 2023)
Background: Although the etiology of women’s cancer has been extensively studied in the last few decades, there is still little evidence comparing the temporal pattern of these cancers among different populations. Methods: Cancer incidence and mortality data from 1988 to 2015 were extracted from the Changle Cancer Register in China, and cancer incidence data for Los Angeles were extracted from Cancer Incidence in Five Continents plus database. A Joinpoint regression model was used to analyze the temporal trends of incidence and mortality for breast, cervical, corpus uteri and ovarian cancers. The standardized incidence ratios were applied to compare the cancer risk across populations. Results: An increasing trend of incidence rate for breast, cervical, corpus uteri and ovarian cancer was observed in Changle, although the rate leveled off for breast and cervical cancer after 2010. The mortality rate of breast and ovarian cancer was slightly increased during this period, while we found a decreased mortality of cervical cancer from 2010. The mortality of corpus uteri cancer showed a decreasing and then increasing trend. The incidence of breast, corpus uteri and ovarian cancer in Chinese American immigrants in Los Angeles was significantly higher than indigenous Changle Chinese and lower than Los Angeles whites. However, the incidence of cervical cancer in Chinese American immigrants shifted from significantly exceeding to lower than Changle Chinese. Conclusion: The incidence and mortality of women’s cancers in Changle were generally on the rise, and this study concluded that environmental changes were important factors affecting the occurrence of these cancers. Appropriate preventive measures should be taken to control the occurrence of women’s cancers by addressing different influencing factors.